Correlation Serum Ferritin and Peroxidative Index with Pulmonary Function Pediatric Beta Thalassemia Major - Kusumaningtyas, Prabandari; Khairiyadi, Khairiyadi; Suhartono, Eko; Marhaeni, Wulandewi; Hidayah, Nurul (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Background: Beta thalassemia major is a genetic disorder that leads to abnormal hemoglobin production, requiring regular blood transfusions. A common complication is iron overload, which potentially damaging vital organs including the lungs. Oxidative stress due to iron overload is suspected to impair pulmonary function via lipid peroxidation. Objective: This study aims to analyze the correlation between serum ferritin levels and the peroxidative index with pulmonary function in pediatric patients with beta thalassemia major undergoing routine transfusions at RSUD Ulin Banjarmasin. Methods: This study was an analytical observational study with a cross-sectional approach involving children aged 6â€“18 years. Measured parameters included serum ferritin, peroxidative index (H2O2 to catalase ratio), and pulmonary function spirometry (FEV1/FVC ratio). Result: The Pulmonary dysfunction was identified in 68.85% of subjects, predominantly restrictive (65.57%). Mean ferritin level was 5,423.23±3,139.96 µg/L and mean peroxidative index was 46.42±66.38. There was no statistically significant correlation between serum ferritin (p = 0.239) or peroxidative index (p = 0.147) with pulmonary function. Conclusion: Although elevated ferritin and peroxidative index were observed, no significant association was found with pulmonary dysfunction. Monitoring these parameters may aid in early detection and management of pulmonary complications in thalassemia.